Comparative Analysis of Conventional RCC Structure and Diagrid Structure of U-Shape Plan (International Journal of Innovative Research in Engineering & Management, 2023)
Present trends show that the geometrical  configuration of the diagrid structural system to be used  for high-rise buildings provides aesthetic potential and  structural efficiency. The construction of multi-story  buildings is increasing worldwide. To counteract the  lateral forces, one of the effective ways is to adopt a  Diagrid Structural System which also sums up the  aesthetics of the building. Lateral loads in diagrid  buildings are resisted by inclined members which are  placed at the exterior of the building. In this work, the  concrete diagrid structure is analysed and compared with  the conventional concrete building according to  earthquake conditions. This paper considers G+3, G+11  and G+19 storey RC buildings with plan size 15 m x15 m  located in zones II and III for analysis. ETABS 17  software is used for the study of structural members. This  paper compares maximum storey displacement, maximum  storey drift, storey stiffness, shear force and bending  moment with different results.
Keywords: RCC Structure; Conventional RCC Structure; Diagrid Structure; U-Shape Plan